A model-based algorithm to estimate body poses using stereo vision - Muhlbauer, Q.; Kuhnlenz, K.; Buss, M. (RO-MAN 2008 - The 17th IEEE International Symposium on Robot and Human Interactive Communication, 2008)
Estimating the human body pose is of great interest for many tasks, such as human robot interaction, people tracking and surveillance. During the recent years, several approaches have been presented, which still have weaknesses regarding occlusions or complex scenes. In this paper, we present a novel algorithm for human body pose estimation using any three-dimensional representation of the environment, like stereo vision. The presented algorithm is able to leave out body parts and is therefore able to deal with occluded body parts. In a first step, possible humans need to be detected, e.g. by using a skin color filter. A disparity map containing depth information is computed using a stereo matching algorithm. It leads to a three-dimensional representation of the scene. Starting with the detected skin parts, our algorithm segments this point cloud into smaller clusters. The possible matches are then verified, and the body pose is estimated using a kinematic human model with 28 degrees of freedom. As our algorithm is capable of dealing with arbitrary three-dimensional representations, it can easily be adapted to use a three-dimensional laser range finder instead of a stereo camera system.